Revisiting English Competence at Hotel - Afrianto Afrianto; Ingatan Gulö (Universitas Teknokrat Indonesia, 2019)
This study aims at coming up with English competence at hotel. Going along with that aim, this study focuses on one hotel in Bandar Lampung which has been developing; it is Novotel hotel. This chosen hotel meets with the criteria of hotel targeted. Further, this study was conducted qualitatively because it pursued deep findings dealing with English competence of some duties in hotel, such as reception and handling guest. Besides, questioner was employed to gather data and then interview was also conducted to have more concrete data. At last, this study came up with the detail findings of the average of English proficiency based on the positions. Furthermore, this study formulated the common expressions used to host and serve customers.